Can we talk about crisis from libraries? - Anglada, Lluís (Anuario ThinkEPI, 2012)
Will the crisis affect libraries? Can we defend libraries in times of crisis? This paper argues that we can answer yes to both questions. The crisis will affect libraries and one form of influence would be that we come to believe that in these times of scarcity we cannot defend libraries against needs of higher priority. Professionals must communicate what libraries contribute to society and the cost-efficiency of modern libraries. This is the role of professional associations, professionals and libraries. Three reasons to strengthen libraries are outlined: they enable and enhance personal growth and support self-taught learning; are public places not based on consumption; and assist the poor and contribute to social inclusion.